PENINGKATAN PERTUMBUHAN Pueraria javanica YANG DIINOKULASI FUNGI MIKORIZA ARBUSKULA DAN APLIKASI VERMIKOMPOS - Arif, Asrianti (Jurnal Agroteknos, 2011)
The increase in plant productivity can be achieved by improving the quality of marginal lands (such as dried land, stone land, and mining lands). The efforts of land improvement include planting legume plant, application of organic fertilizer and introducing biological agent like Arbuscular Mycorrhiza Fungi (AMF). The combination of legume plant, AMF inoculation and vermicompost could be an effective method and need to be site tested. A pre-evaluation in finding the compatible AMF type to host and obtaining the best composition of vermicompost to Pueraria javanica growth has been conducted in a green house. This research was factorial experiment in CRD using two factors. The first factor was AMF inoculum type and the second factor was medium formulation. The growth factors measured were plant height, root dry weight, shoot dry weight, total dry weight and AMF propagule number. The research revealed that 20% AMF type of Glomus sp. combined with vermicompost composition treatment + 80% zeolit was the best treatment and capable of increasing root, shoot and total plant dry weights by 377%, 90%, and 704%, respectively, compared to the control. AMF inoculum type G. etunicatum (selected) and Glomus sp. (endogenous) gave different responses againts vermicompost addition in which type G. etunicatum was more tolerant than Glomus sp (endogenous). The best inoculum were Glomus sp, G.etunicatum and 30 % AMF type Glomus sp combined with vermicompost composition + 70% zeolit treatment, which produced propagule amount 10120 x 104, 308 x10, 77 x 104 per 100 g zeolit, respectively Key words : Pueraria javanica, Arbuscular Mycoriza fungi, vermikompost